2011
DOI: 10.1136/bmj.d2333
|View full text |Cite
|
Sign up to set email alerts
|

Patient participation groups

Abstract: NHS reforms offer new and wide ranging opportunities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Nevertheless, within Equity and Excellence, 7 PPGs were seen as a potentially important tool for ensuring the patient voice was heard within the proposed structures. 159 To incentivise GP practices, a 2-year Patient Participation DES was implemented in 2011. 141,160 There was evidence from all our case studies that this had had a significant impact on developing these groups, and was seen by some as the most important PPEI initiative at that time.…”
Section: Doi: 103310/hsdr02440mentioning
confidence: 99%
“…Nevertheless, within Equity and Excellence, 7 PPGs were seen as a potentially important tool for ensuring the patient voice was heard within the proposed structures. 159 To incentivise GP practices, a 2-year Patient Participation DES was implemented in 2011. 141,160 There was evidence from all our case studies that this had had a significant impact on developing these groups, and was seen by some as the most important PPEI initiative at that time.…”
Section: Doi: 103310/hsdr02440mentioning
confidence: 99%
“…PRGs are bound by the Patient Participation DES contract rules, with concerns of a more limited remit focusing exclusively on the six steps identified within the DES contract. 7 There are a number of issues related to the typologies identified (Figure 2). For example, a practice-led, virtual group may focus on customer feedback; however, this can dilute patient experience to overall satisfaction, which may distort particular areas meriting improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The National Association for Patient Participation (NAPP) believe that over 75% of general practices in England now have a PRG, 7 with groups still developing. Findings from CS1 data would suggest that financial incentive and the 'must-do' nature of PPIE in general practice has had a direct impact on the increased proliferation of PRGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 This diversity makes it harder to assess their impact. 7 Several studies have identified practical challenges in establishing and sustaining groups. 6 8-10 They face recruitment difficulties and membership is seldom representative of the patient population, in terms of age and ethnicity.…”
Section: What We Know About Patient Participation Groupsmentioning
confidence: 99%